2018
DOI: 10.1111/jbfa.12320
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mandatory IFRS reporting on institutional trading costs: Evidence from Australia

Abstract: This study examines the impact of mandatory International Financial Reporting Standards (IFRS) on the market quality of the Australian Securities Exchange (ASX) 200 constituent stocks. Using traditional metrics that are consistent with prior literature (i.e., bid‐ask spreads), the first stage analysis confirms that stock liquidity has improved. However, when the analysis is extended to consider the trading costs incurred by market participants (i.e., execution shortfall), results suggest liquidity has not chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Abad et al (2017) claim that the liquidity benefits of IFRS adoption can also appear in a weaker reporting enforcement regime, like Spain. Outside the EU, Lepone and Wong (2018) studied the impact of IFRS adoption in a sample of Australian firms. Consistently, they found that both quoted and trade-weighted spreads decreased under IFRS reporting.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Abad et al (2017) claim that the liquidity benefits of IFRS adoption can also appear in a weaker reporting enforcement regime, like Spain. Outside the EU, Lepone and Wong (2018) studied the impact of IFRS adoption in a sample of Australian firms. Consistently, they found that both quoted and trade-weighted spreads decreased under IFRS reporting.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…They show that market liquidity, equity valuation, and the cost of capital improved after IFRS adoption (market liquidity and equity valuation increased, whereas the cost of capital decreased). Lepone and Wong (2018) find IFRS adoption reduces the bidask spread of Australian stocks, and Charoenwong, Chong, and Wang (2014) show the relationship between asset liquidity and stock liquidity is reduced due to improved transparency after IFRS adoption.…”
Section: Related Literaturementioning
confidence: 99%
“…Total transaction costs of large block trades indicate that improvements in market quality also have benefited large institutional traders. Lepone and Wong (2018) examine the impact of mandatory International Financial Reporting Standards (IFRS) on the market quality of the Australian Securities Exchange (ASX) 200 constituent stocks. In the era of High Frequency Trading (HFT) and occurrences of 'fleeting' liquidity, the authors provide some evidence that while IFRS may have enhanced 'visible' bid-ask spreads, tangible liquidity for market participants, particularly global institutional investors, has not improved significantly, echoing the findings in Brogaard, Hendershott, Hunt, and Ysusi (2014).…”
Section: Institutional Trading and Market Microstructurementioning
confidence: 99%